Pengembangan Media Pembelajaran Papan Pintar Malo Maretong dalam Meningkatkan Kemampuan Berhitung Anak Usia 5-6 Tahun - Resta Putri Zega; Adiani Hulu; Endang Junita Sinaga (Ta'rim: Jurnal Pendidikan dan Anak Usia Dini, 2024)
This research aims to develop a new learning media called "Malo Maretong" which can improve the numeracy skills of children aged 5-6 years. This research uses research and development (R&D) methods by applying the ADDIE (Analysis, Design, Development, Implementation, and Evaluation) model. There are five steps in this development, but researchers focus on the first four: analysis, design, development, and implementation. This research involves literature study, validation by experts, as well as product evaluation and revision. Data was collected through questionnaires conducted by media experts, language experts and early childhood experts. Malo Maretong was successfully developed as an effective learning medium to improve the numeracy skills of children aged 5-6 years. The assessment from media experts received an average of 3.9 with a feasibility percentage of 97% and a "very feasible" category. The assessment from linguists received an average of 3.2 with an eligibility percentage of 80% and the "decent" category. The assessment from early childhood experts received an average of 3.2 with a feasibility percentage of 80% and the "decent" category. The validation results showed a very positive assessment from experts with a high average rating and a "very feasible" category. After validation by experts, product revisions and small-scale trials were carried out. The results of the small-scale trial showed an average assessment of 3.7 with a feasibility percentage of 93% and a "very feasible" category. This research makes an important contribution to the development of learning media that suits the needs and characteristics of early childhood, and provides strong recommendations for the implementation of Malo Maretong in the learning context of children aged 5-6 years.